2021
DOI: 10.1051/mbcb/2021007
|View full text |Cite
|
Sign up to set email alerts
|

Position of posterior superior alveolar artery in relation to the maxillary sinus using cone beam computed tomography in Indian sub-population

Abstract: Purpose: To assess the location of posterior superior alveolar artery (PSAA) using CBCT in relevance to sinus lift procedure for implant placement. Patients and Methods: A retrospective study was conducted using the CBCT data of 500 patients (n = 500). Linear measurements were carried out to localize the medio-lateral and vertical position of posterior superior alveolar artery in postero-lateral wall of maxillary sinus and its proximity to the floor of maxillary sinus using CS 3D imaging 3.7.0 software program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…In the review, 6 characteristics of the PSAA were investigated. A total of 34 1 9 10 12 13 14 15 16 17 18 20 21 23 24 25 26 27 28 29 30 31 32 33 34 35 41 61 62 63 64 65 66 67 68 studies examined the detection of the artery, 27 studies analyzed its diameter, 1 12 13 14 15 16 18 19 20 21 23 24 26 28 31 32 33 35 41 61 62 63 65 66 67 68 69 25 studies investigated its location, 1 10 12 13 14 15 16 17 20 21 25 26 27 29 31 32 33 34 41 62 <...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the review, 6 characteristics of the PSAA were investigated. A total of 34 1 9 10 12 13 14 15 16 17 18 20 21 23 24 25 26 27 28 29 30 31 32 33 34 35 41 61 62 63 64 65 66 67 68 studies examined the detection of the artery, 27 studies analyzed its diameter, 1 12 13 14 15 16 18 19 20 21 23 24 26 28 31 32 33 35 41 61 62 63 65 66 67 68 69 25 studies investigated its location, 1 10 12 13 14 15 16 17 20 21 25 26 27 29 31 32 33 34 41 62 <...…”
Section: Resultsmentioning
confidence: 99%
“… 11 However, numerous original articles have been published during this period. 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 These studies have revealed a broad range of detection rates for this artery using CBCT. 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 For instance, in the Iranian population, the detection rate varies between 25% 27 and 93%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the parameter of the mean diameter, Albuquerque et al found a measure of 1.32 mm, while Alves et al found a measure of 1.16 mm, and Tran et al [ 43 ] found an average diameter of 0.91 mm. Finally, in 2021, Fayek et al [ 44 ] and Godil et al [ 45 ] found a frequency of 92% with a mean diameter of 1.0 mm and a frequency of 99.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In scientific literature, authors use different anatomical terms to refer to this structure, such as PSAA (Jung et al, 2011;Cruz Ibañez et al, 2016), Intraosseous Ramus of the PSAA ( de Oliveira et al, 2017), Intraosseous Rami (Duruel et al, 2019), Intramural Artery (Godil et al, 2021), Alveolar Antral Artery (AAA) (Alves & Cândido;Alves, 2017;Alves et al, 2020), etc. Considering the variety of terms used to name this vascular structure, the object of this study was to carry out a systematic review of the terms used.…”
Section: Introductionmentioning
confidence: 99%